Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1074/jbc.m109.047209
|View full text |Cite
|
Sign up to set email alerts
|

PAX6 Is Expressed in Pancreatic Cancer and Actively Participates in Cancer Progression through Activation of the MET Tyrosine Kinase Receptor Gene

Abstract: Tumors of the exocrine pancreas have a poor prognosis. Several proteins are overexpressed in this cancer type, including the MET tyrosine kinase receptor and the transcription factor PAX6. In this report, we find that PAX6(5a), an alternately spliced variant form of PAX6, is expressed in pancreatic carcinoma cell lines at higher levels than the canonical PAX6 protein. Both protein forms of PAX6 bind directly to an enhancer element in the MET promoter and activate the expression of the MET gene. In addition, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…These experiments showed that decreased Pax6 expression resulted inremarkable suppression of in vitro cell growth and in vivo tumorigenesis. Our observations were in consistency with that in previous report about pancreatic cancer (13). Disturbed regulation of the cell cycle is a hallmark of cancers.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These experiments showed that decreased Pax6 expression resulted inremarkable suppression of in vitro cell growth and in vivo tumorigenesis. Our observations were in consistency with that in previous report about pancreatic cancer (13). Disturbed regulation of the cell cycle is a hallmark of cancers.…”
Section: Discussionsupporting
confidence: 83%
“…It should be noted that Pax6 has three different protein isoforms: normal Pax6, Pax6 (5a), and paired domain-less Pax6 (ΔPD) (20). Thereinto, Pax6 (5a) is expressed in pancreatic carcinoma cell lines at higher levels than the canonical Pax6 protein (13). Yet it is still unknown if there is any difference in expression levels or functional roles in breast cancer for individual variants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PAX6 was upregulated in alveolar soft part sarcoma, a type of cancer with an extremely poor prognosis (20). In pancreatic cancer, PAX6 actively participates in tumor growth via the MET tyrosine kinase (21). However, certain studies have suggested that PAX6 may have a tumor suppressor effect, such as in glioblastoma (22,23).…”
Section: Discussionmentioning
confidence: 99%